Data science research and practice: High time for synergy. Issue 1 (18th October 2019) - Rorissa, Abebe; Federer, Lisa; Hagen, Loni; Kim, Jeonghyun (Annie); Andrews, James
ABSTRACT: Rapid increase in the rate of information and communication technology innovations resulted in the Big Data phenomenon and, in turn, led to challenges in data curation, management, processing, access, preservation, and dissemination. To effectively address these challenges, synergistic collaborations and partnerships between researchers and practitioners need to be established. For research to inform practice, and vice versa, the ASIS&T community, specifically those engaged in data science research and practice, need to regularly share their ideas, issues, findings, and best practices so that this young sub‐discipline can grow and thrive. We believe a suitable time has arrived for all stakeholders to deliberate on how best to create synergy between researchers and practitioners in order to help set the agenda for the near and distant future. To that end, we are proposing an interactive panel where panelists will lead a discussion by researchers and practitioners to identify any gaps with respect to data science research and practice to collaboratively find ways to address them.